Sexual dimorphism in exposure to particulate matter (PM2.5) and residential radon (Rn), and its association with incidence rates of TB and lung cancer (CaP) in the 43 districts of Metropolitan Lima - Ordoñez-Aquino, Carol (2025)
Introduction: Previous studies have associated exposure to fine particulate matter (PM2.5) with higher rates of tuberculosis (TB), especially among men. Likewise, a causal relationship between TB and lung cancer (LC) has been demonstrated. On the other hand, residential radon gas (²²²Rn) is a well-known carcinogen and the leading cause of LC among non-smokers. Objective: To evaluate the ecological association between PM2.5 and/or ²²²Rn levels and tuberculosis (TB) and lung cancer (LC) rates in adults over 60 years of age of both sexes, in the 43 districts of Metropolitan Lima, during the period 2019–2022. Materials and Methods: A cross-sectional observational study using secondary data analysis. TB and LC data were obtained from the Ministry of Health, PM2.5 estimates were derived using the WRF-Chem model, and ²²²Rn concentrations were measured with G2 diffusion chambers. For the associative analysis, negative binomial regression models were constructed using STATA statistical software version 18.0. Results: A positive association was observed between lung cancer (LC) and the top tertile of TB rates (IRR: 1.61; 95%CI: 1.12–2.29), although there was no evidence of an inverse relationship. Exposure to PM2.5 was associated with PC in males (IRR: 1.02; 95% CI: 1.00–1.02), while exposure to ²²²Rn showed a significant association with PCa in both sexes (female IRR: 1.44; Male IRR: 1.34). In women, only ²²²Rn was associated with PC; in males, independent associations with PM2.5, TBC, and ²²²Rn were identified. Conclusions: The results suggest a possible sexual dimorphism in the ecological relationship between the exposure factors evaluated and lung cancer (LC) rates, with the districts with the highest rates being more frequently associated with males.